In-situ detection of LiMn2O4 dissolution during electrochemical cycling by. (1st August 2021) - Wang, Jialong; Islam, Md Monirul; Donne, Scott W.
Abstract: Herein we describe a modified Swagelok electrochemical cell for characterizing individual electrode behavior as part of full cell operation, including individual electrode potentials and dissolution phenomena. The case study presented is that of the non-aqueous Li-LiMn2 O4 system. Outcomes from the work include characterization of lithium negative electrode potential variation with applied current, lithium corrosion and passivation in the electrolyte, and LiMn2 O4 dissolution with cycling. It is also demonstrated that Mn(III) is the dissolution product. Application of the technique to other systems, including electrode materials and electrolytes, is discussed.